The Role of Jordanian Teachers in Promoting an Islamic Culture of Tolerance from First-Semester Students’ Point of View - Al-Momani, Mohammad; Hamadat, Mohammad Hassan; Murtada, Mariam Ayed; Rababa, Elham Mahmoud (Millah: Journal of Religious Studies, 2024)
This study aims to identify the role of Jordanian teachers in promoting an Islamic culture of tolerance from the perspective of basic-stage students in Jordan. It also aimed to determine the difference between the students’ opinions regarding their views and the role of the Jordanian teacher in promoting the Islamic culture of tolerance according to the gender and geographical location of the school. This study used quantitative and descriptive approaches, in which the data were collected using a questionnaire consisting of 28 items. The questionnaire was distributed to a sample of 1,000 male and female students in the first semester of the year 2023/2024. After conducting the necessary statistical treatments, 19 items in the questionnaire received a high score and nine items received a moderate score. Furthermore, the questionnaire showed a high score for the scale, with a mean of 2.76 and a standard deviation of 0.62. The results of the study showed no statistically significant differences depending on the gender variable, while the results of the study showed that existence differences function statistically be consoled for the variable of the geographical location of the school and in favor of the school in the village.